Sexual Satisfaction in Fully Ambulatory People with Multiple Sclerosis: Does Disability Matter? - Pawel Dobrakowski; Agnieszka Machowska-Majchrzak; Beata Labuz-Roszak; Ewa Niewiadomska; Krystyna Pierzchala (Behavioural Neurology)
Primary sexual dysfunctions (SD) are a direct result of neurological changes that affect the sexual response. Secondary SD result from the symptoms that do not directly involve nervous pathways to the genital system, such as bladder and bowel problems, fatigue, spasticity, or muscle weakness. Tertiary SD are the result of disability-related psychosocial and cultural issues that can interfere with sexual feelings and experiences. The aim of this study was to assess the sexual satisfaction (SS) in people with multiple sclerosis (PwMS) without significant mobility impairment and to estimate the influence of SD, the score on the Kurtzke Expanded Disability Status Scale (EDSS), lowered mood, and stress coping strategies on SS. Methods. 76 PwMS with the EDSS score<5.0 points were enrolled in the study. The subjects completed the Montgomery-Asberg Depression Scale (MADRS), the Coping Inventory for Stressful Situations (CISS), the Multiple Sclerosis Intimacy and Sexuality Questionnaire (MSISQ-19), and the Sexual Satisfaction Questionnaire (SSQ). Results. The level of SS in PwMS was not significantly lower compared to that of the general population. It correlated with the primary, secondary, and tertiary SD and lowered mood. However, it did not correlate with disability measured by the EDSS. Conclusions. The level of SS in PwMS with the EDSS score below 5.0 points was not significantly lower. SS depended on SD, lowered mood, and stress coping style, and it was not significantly related to the level of disability in patients with the EDDS score below 5.0.